Synthesis and Characterization of New Palladium(II) Complexes with Ligands Derived from Furan-2-carbaldehyde and Benzaldehyde Thiosemicarbazone and their in vitro Cytotoxic Activities against Various Human Tumor Cell Lines - Hernández Gorritti, Wilfredo Román (2010)
With the ligands 4-phenyl-1-(furan-2-carbaldehyde)thiosemicarbazone, HTSC1,(1), 4-phenyl-1-(5'-phenyl-furan-2-carbaldehyde)thiosemicarbazone, HTSC2(2),o-methoxy-benzaldehydethiosemi-carbazone, HTSC3(3), ando-cyano-benzaldehydethiosemicarbazone, HTSC4(4), the correspondingpalladium(II) complexes, Pd(TSC1)2(5), Pd(TSC2)2(6),Pd(TSC3)2(7), and Pd(TSC4)2(8)weresynthesized and characterized by elemental analysis and spectroscopic techniques. The crystal struc-ture of Pd(TSC3)2(7) was determined by single-crystal X-ray diffraction. Complex7shows a square-planar geometry, where two deprotonated ligands are coordinated to the PdIIcenter through the ni-trogen and sulfur atoms in atransarrangement.In vitroantitumor studies against different humantumor cell lines have revealed that the palladium(II) complexes5–8are more cytotoxic (IC50valuesin the range of 0.21 – 3.79µM) than their corresponding ligands (1–4)(>60µM). These resultsindicate that the antiproliferative activity is enhanced when thiosemicarbazone ligands are coordi-nated to the metal. Among the studied palladium(II) complexes,8exhibits high antitumor activity onK562 chronic myelogenous leukemia cells with a low value of the inhibitory concentration (IC50=0.21µM)